2015
DOI: 10.1681/asn.2015040341
|View full text |Cite
|
Sign up to set email alerts
|

Change in Measured GFR Versus eGFR and CKD Outcomes

Abstract: Measured GFR (mGFR) has long been considered the gold standard measure of kidney function, but recent studies have shown that mGFR is not consistently superior to eGFR in explaining CKD-related comorbidities. The associations between longitudinal changes in mGFR versus eGFR and adverse outcomes have not been examined. We analyzed a subset of 942 participants with CKD in the Chronic Renal Insufficiency Cohort Study who had at least two mGFRs and two eGFRs determined concurrently by iothalamate and creatinine (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 51 publications
2
38
0
2
Order By: Relevance
“…Furthermore, the CKD-EPI is a better prognosticator of ESRD and mortality outcomes. 8,26 Similar to the findings of our study, the global estimate of CKD was lowered by 24% when CKD-EPI was used instead of the MDRD equation. 8 Although it would identify some patients as having CKD that MDRD would not, the net persons identified with CKD would be less using the CKD-EPI equation.…”
Section: Original Research and Contributionssupporting
confidence: 86%
“…Furthermore, the CKD-EPI is a better prognosticator of ESRD and mortality outcomes. 8,26 Similar to the findings of our study, the global estimate of CKD was lowered by 24% when CKD-EPI was used instead of the MDRD equation. 8 Although it would identify some patients as having CKD that MDRD would not, the net persons identified with CKD would be less using the CKD-EPI equation.…”
Section: Original Research and Contributionssupporting
confidence: 86%
“…Also, eGFR measurements were not uniformly spaced, a weakness that favors detection of too many rather than too few nonlinear trajectories as they become unstable in areas with sparse observations. Finally, we acknowledge that direct GFR measurements were not available in our patients; however, a recent study found that measured GFR compared with eGFR did not show an enhanced association with risk of ESRD, cardiovascular events, or death (39). …”
Section: Discussionmentioning
confidence: 96%
“…Finally, we decided to estimate rather than to measure GFR because measuring GFR in such a large sample size would be logistically challenging. In addition, measured GFR may have more variation than eGFR, introducing DOI: 10.1159/000490261 a larger error when using differences between 2 timepoints [49].…”
Section: Discussionmentioning
confidence: 99%